Juridical Review of Cyber Security Mobile Banking Digitalization Process For Legal Protection of Customers - Florentina Dani Eti Kusuma Eko Wardani; R. Febriarto Fadjar; Mychelvia Vrelya JohnLearn (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
Indeed, the emergence of the bank's digitalization process does not necessarily eliminate the possibility of errors in its operation., both intentional and unintentional errors, one of the intentional errors is Fraud and/or cybercrime (as a crime that occurs through or on computer networks on the internet) in electronic services from this digitalization, which causes losses to other parties in the case of Digital Banks is the customer. Therefore, the purpose of this paper is to analyze the Security System of Digital Banking Services and Responsibility for Electronic Transactions of Digital Banking Services. In analyzing, the juridical-normative research method is used. The results showed that the realization of legal protection against customers for fraud or cybercrime that occurs in Digital Bank transaction activities can be seen from how the efforts of the government and the Authority in the Financial Services sector regulate and limit various interests and powers so that they do not collide with each other and are optimally organized. Commercial Banks are required to carry out their business activities prudently and implement Good Corporate Governance, Risk Management, and Consumer Protection will be better prepared to face various kinds of risks arising from the provision of Mobile Banking services, because if this is not done, the loss will be felt not only by service users but the Commercial Bank itself as a service provider, as can be seen in the case example in the decision.